“I feel like I don't matter because of my status as a person”— A mixed-methods, cross-sectional study of emergency department care experiences among equity-deserving groups in Ontario, Canada - Walker, Melanie; MacKenzie, Meredith; Douglas, Stuart L.; Collier, Amanda; Pritchard, Jodie; Hoffe, Sharleen; Norman, Patrick A.; Purkey, Eva; Messenger, David; Bartels, Susan A. (Frontiers in Disaster and Emergency Medicine, 2024)
Background -Equity-deserving groups (EDGs) have increased emergency department (ED) use, and often report negative ED care. Past studies have largely been qualitative and suffer from methodological bias and lack of comparison groups, thereby limiting their identification of interventions to ensure equitable care among equity-deserving populations. This study sought to better understand ED care experiences among EDGs in our local setting. Materials and Methods -We conducted a community-engaged, mixed-methods cross-sectional study using sensemaking methodology at the Kingston Health Sciences Centre's ED and Urgent Care Centre (Ontario, Canada), as well as at community partner organizations. From June-August 2021, eligible participants were invited to complete a survey about an ED care experience within the previous 24 months. Multiple-choice questions collected demographic/ED visit information including selfidentification with up to three EDGs (Indigenous; having a disability; experiencing mental health concerns; persons who use substances (PWUS); 2SLGBTQ+; people who experience homelessness (PWEH); a visible minority; or having experienced violence). We evaluated differences in overall ED care experiences by EDG self-identification using chi squared tests. Quantitative analysis of survey questions disaggregated by EDG status, and a thematic analysis of participant experiences are presented. Results -Overall, 1973 unique participants completed the survey (949 controls and 994 EDGs) sharing 2114 ED care experiences in total. Participants who identified as PWUS, having mental health concerns, 2SLGBTQ+, PWEH, or having a disability, reported more negative overall experiences (p<0.001). Compared with controls, each of the eight EDGs were statistically more likely to report feelings of judgement/disrespect, that there was too little attention paid to their needs (p<0.001) and that it was more important to be treated with kindness/respect than to receive the best possible care (p<0.001). Thematic analysis supported quantitative findings and identified four themes: stigma/judgement, poor staff communication, lack of compassionate care, and patients feeling unsupported. Discussion -Negative ED care experiences were pervasive among EDGs including feelings of judgement/stigma and a perception that a better understanding of personal situation/identity/culture was needed to improve care. Qualitative findings identified the following future interventions: universal trauma-informed care, improved care for addiction/substance use, and improved access to mental health care resources.